1973
DOI: 10.1901/jeab.1973.20-197
|View full text |Cite
|
Sign up to set email alerts
|

OBSERVING STIMULUS SOURCES THAT SIGNAL FOOD OR NO FOOD1

Abstract: Pigeons were given a choice between observing a stimtllus source that was uncorrelated with food or one that was informative. The informative source wvas either positive, in which a stimulus change signalled food, or negative, in which change signalled no food. If observing is supported by the reduction of uncertainty, the negative as well as the positive source should be preferred to the uncorrelated source. On the other hand, if observing requires support by conditioned reinforcement, the negative source sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
2

Year Published

1974
1974
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 11 publications
4
29
0
2
Order By: Relevance
“…Periodic observations revealed that the rats of both groups tended to restrict their activities to parts of the apparatus away from the CS source. Similar withdrawal from a localized CS was also obtained in pigeons when the CS predicted the absence of food (Hearst Sc Franklin, 1977; Jenkins & Boakes, 1973). …”
Section: Stimuli Signaling Aversive Reinforcerssupporting
confidence: 53%
“…Periodic observations revealed that the rats of both groups tended to restrict their activities to parts of the apparatus away from the CS source. Similar withdrawal from a localized CS was also obtained in pigeons when the CS predicted the absence of food (Hearst Sc Franklin, 1977; Jenkins & Boakes, 1973). …”
Section: Stimuli Signaling Aversive Reinforcerssupporting
confidence: 53%
“…A plausible account is that the CS-US relation induces approach tendencies toward cues that predict the US, and withdrawal from cues predicting no-US, relative to uninformative cues, as suggested by our observations (cf. Figure 7) and previous research (e.g., Hearst & Franklin, 1977;Jenkins & Boakes, 1973;Wasserman et al, 1974). These tendencies, in tum, placed the bird at different distances from the food magazine in the present situation, as reflected in latency.…”
Section: Resultssupporting
confidence: 67%
“…Other work in autoshaping has revealed that behavior directed toward the stimulus most highly correlated with reinforcement will ordinarily arise if the stimulus is easily localized (e.g., Allaway, 1971;Bilbrey and Winokur, 1973;Brown and Jenkins, 1968;Gamzu and Schwartz, 1973;Williams, 1971, 1973;Jenkins and Boakes, 1973;Peterson, Ackil, Frommer, and Hearst, 1972;Schwartz, 1973;Wasserman, 1973aWasserman, , b, 1974Wasserman, Franklin, and Hearst, 1974;Wasserman and McCracken, 1974). Furthermore, behaviors directed away from a localized stimulus signalling nonreinforcement may also arise in autoshaping studies (see Jenkins and Boakes, 1973;. These autoshaping findings correspond closely with those of operant discrimination studies in which "feature-positive" subjects peck at the distinctive feature and "feature-negative" subjects peck away from it.…”
Section: Resultsmentioning
confidence: 99%